2012
DOI: 10.1002/ibd.21925
|View full text |Cite
|
Sign up to set email alerts
|

Majority of patients with inflammatory bowel disease in clinical remission have mucosal inflammation

Abstract: A large proportion of IBD patients have mucosal inflammation without clinical symptoms. Although one-third recover spontaneously, mucosal inflammation in patients who are clinically in remission is associated with more severe mucosal disease activity, but not with more complications or symptomatic flares during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
110
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(115 citation statements)
references
References 22 publications
4
110
1
Order By: Relevance
“…Generally speaking, this could mean that up to 40% of patients who are clinically in remission have mucosal inflammations. Similarly, Baas et al reported that 34% of IBD patients who were clinically in remission had both endoscopic and histological inflammation; 34% had histological inflammation, and only 2 of their 151 patients had endoscopic lesions [21]. These findings are important issues for predicting future relapse in patients who appear to be in clinical remission.…”
Section: Discussionmentioning
confidence: 97%
“…Generally speaking, this could mean that up to 40% of patients who are clinically in remission have mucosal inflammations. Similarly, Baas et al reported that 34% of IBD patients who were clinically in remission had both endoscopic and histological inflammation; 34% had histological inflammation, and only 2 of their 151 patients had endoscopic lesions [21]. These findings are important issues for predicting future relapse in patients who appear to be in clinical remission.…”
Section: Discussionmentioning
confidence: 97%
“…Reports from practice fail to show significant histological absence of inflammation in UC patients in remission. Baars et al reported that 63% of their cohort of 98 UC patients in remission had histological inflammation, and 20% had at least moderate inflammation, using a non-validated scale [13]. Recently, Rosenberg et al found that histological features of inflammation were found in 54% of UC patients receiving maintenance therapy, and 37% had at least moderate inflammation based on histology scores [15].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the severity of histological inflammation as an endpoint for drug therapy has not been part of standard clinical practice, although persistent endoscopic and histological inflammation in the absence of clinical symptoms is common [13,14]. Patients with quiescent UC with histological inflammation are difficult to identify because endoscopic measures of inflammation have a variable correlation with symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…18,26,27,[49][50][51][52][54][55][56][60][61][62][63][64][65][66][67] This systematic review and that of Mosli et al, has identified 22 histological scoring systems for UC. 44 The first described was that by Truelove and Richards in 1956 in a study of 111 serial biopsy specimens from 42 patients with UC.…”
Section: Histological Scoring Systemsmentioning
confidence: 99%